Dental plaque and calculus: risk indicators for their formation - Christersson, L A; Grossi, S G; Dunford, R G; Machtei, E E; Genco, R J (Journal of dental research, 1992)
The aim of this study was to determine the levels of plaque and subgingival calculus accumulation and to evaluate their correlations with periodontal disease, as well as to evaluate the correlations with race, age, and gender in an attempt to identify risk indicators for plaque and calculus formation. A total of 508 adults 25-73 years of age was examined, and plaque assessment, gingival bleeding assessment, probing pocket depth, and attachment levels were determined. The mean percent visible plaque was 73.5% (range, 8.3-100%), mean percent of bleeding surfaces 38.5% (range, 0-100%), and the mean percent teeth with subgingival calculus 39.6% (range, 0-100%). The mean probing pocket depth in the group was 2.5 +/- 0.6 mm (SD), and mean clinical attachment loss was 2.1 +/- 1.1 mm. The majority (63%) were classified as having "Moderate" periodontal disease, 7% were "Healthy", and the remaining 30% had "Established" periodontal disease. Plaque and calculus showed statistically significant relationships to the three disease categories (p less than 0.001). Multiple step-wise regression analyses on the correlations between plaque and periodontal disease, race, age, and gender resulted in an overall correlation coefficient of r = 0.25 (p less than 0.001). Disease status ("Established") contributed most (p = 0.003), followed by race (Blacks; p = 0.015), gender (Males; p = 0.022), and age (55-73 yr; p = 0.022), to the correlation with plaque. For subgingival calculus, the overall correlation coefficient was r = 0.44 (p less than 0.001). However, only two of the variables--namely, disease status (p less than 0.001) followed by race (p = 0.017)--showed statistically significant correlations.